2018
DOI: 10.1037/tps0000140
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use is associated with intimate partner violence perpetration among men arrested for domestic violence.

Abstract: Intimate partner violence (IPV) is a serious public health problem. Substance use, particularly alcohol, is a robust risk factor for IPV. There is a small but growing body of research demonstrating that marijuana use is positively associated with IPV perpetration. However, research on marijuana use and IPV has failed to control for other known predictors of IPV that may account for the positive association between marijuana use and IPV perpetration. Therefore, the current study examined whether marijuana use w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 50 publications
(89 reference statements)
4
13
0
Order By: Relevance
“…She noted that she once went to the bank, withdrew her money across the counter, and then got a thorough beating from her spouse. These fi ndings are in line with other studies (Anena, Abalo 2019;Shorey et al 2018;Hughes et al 2015) that have argued that -contrary to common belief -economic empowerment can actually increase GBV vulnerability.…”
Section: Socio-cultural Factorssupporting
confidence: 91%
See 1 more Smart Citation
“…She noted that she once went to the bank, withdrew her money across the counter, and then got a thorough beating from her spouse. These fi ndings are in line with other studies (Anena, Abalo 2019;Shorey et al 2018;Hughes et al 2015) that have argued that -contrary to common belief -economic empowerment can actually increase GBV vulnerability.…”
Section: Socio-cultural Factorssupporting
confidence: 91%
“…Patriarchal societies use language, religion, laws, and all other aspects of social conditioning, including violence, to maintain this hierarchical relationship between men and women (Hadi 2017;Garcia 2014;Nkiru 2013;Gonzalez 2004). Such patriarchal social structures can thus not only deepen gender-based inequalities but also deny women access to essential services, thus affecting their well-being (Shorey et al 2018).…”
Section: Socio-cultural Factorsmentioning
confidence: 99%
“…For instance, scholars have observed an association between cannabis and violence in intimate partners [e.g. (103)(104)(105)]. Our team conducted four additional studies to elucidate the association using more robust methodological strategies and wellknown databases in youth populations from the Quebec Health Survey of High School Students (106) and Longitudinal Studies of Child Abuse and Neglect (107) as well as in samples with SMD from the MacArthur Violence Risk Assessment Study (108) and Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) (109).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the alcohol-IPV association, research evidence linking cannabis use with IPV has been less consistent [ 57 ]. For example, among a sample of men arrested for domestic violence, Shorey and colleagues found that cannabis use was significantly associated with IPV even after controlling for alcohol use and problems [ 58 ]. Yet among a sample of those arrested for domestic violence, Stuart et al [ 59 ] found that women were less likely to perpetrate IPV on days in which cannabis was used [ 59 ].…”
Section: Discussionmentioning
confidence: 99%